If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -15 = 35 Reorder the terms: -15 + 6y = 35 Solving -15 + 6y = 35 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 6y = 35 + 15 Combine like terms: -15 + 15 = 0 0 + 6y = 35 + 15 6y = 35 + 15 Combine like terms: 35 + 15 = 50 6y = 50 Divide each side by '6'. y = 8.333333333 Simplifying y = 8.333333333
| (2x+3y)*(4x^2-6xy+9y^2-3)=0 | | 0.75(m−1)−0.5m=5/6(2m−7) | | y-2(1.5+0.5y)=1 | | P=2q+7r | | -2(y+3)+3(3y-7)=6(y-3)+13 | | log[9]7-log[9]10=log[9] | | y^2+8y-16= | | -2(4t-5)+3t=6t-9 | | 0.04*(500+x)=50 | | 7y+3-5y=5+y-5 | | 4x^2-32x=-14 | | 4x^2-32x=-24 | | -8x+10=8-4x-5x | | 3y-5=4y-3 | | 11-2(a-1)=4a+a | | -37+-56= | | 2x/4=7 | | F(x)=3+ln(x) | | 2(2x+1)=5x-9x | | 7x+7=12x+7 | | 17x-6=14x-9 | | -25z-0.1=-35z+1.3 | | 10+18=-4(2x-7) | | 4x+5=9x+25 | | 3.3+x=5 | | x^2+y^2+z=27 | | 9-3(4y+6)=0 | | X+24=9x+56 | | 8=x(x-2) | | X-6=46 | | x/2-314=123 | | 10x-1447=933 |